Waktu Pemulihan Saturasi Oksigen pada Pasien COVID-19 di RSND Semarang: Pengaruh Usia, Derajat Keparahan, dan Komorbiditas - Hapsari, Hererapratita Aysha; Purwoko, Yosef; Basyar, Edwin; Ngestiningsih, Dwi (UI Scholars Hub, 2026)
Introduction. COVID-19 may cause impaired oxygenation that affects the recovery process, making oxygen saturation an important parameter in clinical monitoring. Age, disease severity, and comorbidities are suspected to influence the duration of oxygen saturation recovery. This study aimed to analyze differences in oxygen saturation recovery time based on age, disease severity, and comorbidity status in hospitalized COVID-19 patients. Methods. This was an observational analytic study with a retrospective cohort design using a survival analysis approach. The study was conducted at Diponegoro National Hospital (RSND) Semarang from October to November 2021 using medical records of hospitalized COVID-19 patients from March 2020 to February 2021. A total of 82 patients were selected using consecutive sampling based on inclusion and exclusion criteria. The variables analyzed included age, disease severity, and comorbidity status, with oxygen saturation recovery time as the outcome. Recovery time was defined as the duration (in days) from hospital admission until oxygen saturation (SpO2) ≥95% was achieved in stable condition. Data were analyzed using Kaplan–Meier, log-rank test, and Cox regression. Results. Bivariate analysis showed significant differences in oxygen saturation recovery time based on age (p < 0.001), severity (p < 0.001), and comorbidity status (p = 0.006). Median recovery time was longer in the elderly, those with severe cases, and those with comorbidities. Multivariate analysis showed that only severity was significantly associated with recovery time (HR = 1.98; 95% CI: 1.12–3.48; p = 0.018). Conclusion. There was a significant association between severity and oxygen saturation recovery time.